Values in the evaluation and consideration process - an experimental study on values in a spatial context - Müller, Christin Juliana; Senßfelder, Annabell; Diller, Christian (ERDKUNDE, 2025)
In the spatial context, personal and institutional values are crucial for decision-making and prioritisa-tion. This article takes a perspective on values in spatial research and university practice. The present study deals with an understanding of values and the investigation of the negotiation and adaptation of values in collaborative processes by students. The data obtained from an experimental survey provides an insight into the values that guide students' actions. The results of the study suggest that the values of ‘protecting the environment’, ‘forward-looking’, ‘equality’, ‘common good’, ‘health’ and ‘sustainability’ are considered stable and guiding. However, a transformation of values and a specific prioritisation of values within different demographic and socio-structural characteristics can also be observed. A shift in values occurs during the experimental planning process, which illustrates the transformative effect of planning discourses. The findings contribute to a deeper understanding of value culture and its dynamics, particularly in regard to the orientation towards action and possible conflicts of values in planning processes. The results emphasise the importance of transparent and cooperative planning processes to create a basis for decision-making.